Implementasi Prinsip Good Corporate Governance dalam Struktur Manajemen PT Elnusa Petrofin (EPN) Cabang Jambi - Yawardo, Panji Nugraha; Ermaini; Tamtomo, Hario (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study aims to analyze the implementation of Good Corporate Governance (GCG) principles within the management structure of PT Elnusa Petrofin (EPN) Jambi Branch. The background of this research is based on the importance of applying sound corporate governance principles to maintain transparency, accountability, and operational sustainability in the energy sector. This study employs a descriptive, qualitative approach, collecting data through in-depth interviews, observations, and documentation. The data were analyzed using the interactive model developed by Miles, Huberman, and Saldaña, which encompasses data reduction, data display, and conclusion drawing and verification. The results of the study indicate that the implementation of GCG at PT Elnusa Petrofin Jambi Branch has been carried out effectively and in accordance with the guidelines set by the company’s headquarters, particularly in applying the principles of responsibility and accountability. The principle of transparency is realized through routine reporting systems and internal information disclosure, although communication barriers between units still exist. The principles of independence and fairness have also been implemented through conflict-of-interest prevention policies and a fair reward system. However, challenges remain in employee training and the limited autonomy of the branch in making strategic decisions. Overall, this study concludes that the success of implementing Good Corporate Governance at the PT Elnusa Petrofin Jambi Branch is strongly influenced by management commitment, internal control systems, and an integrity-based organizational culture. These findings are expected to provide theoretical contributions to the development of management science and serve as practical evaluation material for the company in strengthening professional and sustainable corporate governance. Reading comprehension not only helps students understand the content of a text but also trains them to analyze, infer, evaluate, and interpret the information conveyed within it.